Where There's a Will, There's a Way: Synthesizing Creativity, Contagious Motivation, and Unique Projects Into the Course Experience. (April 2022) - Krishen, Anjala S.
Creativity is not just a catch phrase for the new decade—it is a way of life. While technology-driven innovation can promote efforts to produce optimal solutions, individually driven creativity is necessary to launch and drive cutting-edge, trailblazing ideas. The goal of this study is to examine relationships between creative divergent thinking (CDT) and motivation situated within course projects as antecedents to the overall course experience. The synthesis of transformational leadership, context-dependent fixation hypothesis, strength of weak ties perspective, contagious motivation, and constructivist learning frameworks form the interdisciplinary foundation for the proposed contagious motivation and creative experience model (CMCEM ). The proposed marketing classroom model is tested using a structural equation model of N = 540 marketing undergraduate students. Findings indicate that CDT is an important individual characteristic that affects classroom dynamics. Importantly, when students exhibit higher levels of CDT, they perceive higher project uniqueness, higher levels of motivation, higher other student motivation, and more positive course experiences. In addition to other findings, the CMCEM emphasizes the powerful combination of CDT, individual student motivation, the contagious nature of that motivation on other students through well-structured group projects, and the importance of instructors as transformational teachers.